Specific Characteristics of Moral - Aesthetic Values in “Avesto” - Oysuluv Jamoliddinovna Urokova (Researchparks Publishing, 2023)
the history of mankind is the development from simple representations of visions of existence to complex phenomena, development from narrow material needs to contrary spiritual activity. When something surrounds a person, it affects him, is perceived by him and evokes various figurative and spiritual associations. This article analyzes the manifestation of aesthetic views in the “Avesta” historical monument.